Surgical Excision with Forehead Flap as Single Modality Treatment for Basal Cell Cancer of Central Face: Single Institutional Experience of 50 Cases - Jagdeep Rao; Harsh Deora (Journal of Skin Cancer)
Basal cell carcinoma (BCC) is the most common skin cancer worldwide. The WHO has defined it as “a locally invasive, slowly spreading tumor which rarely metastasizes, arising in the epidermis or hair follicles and in which the peripheral cells usually simulate the basal cells of the epidermis.” Here we discuss the management of BCCs of central face with surgical excision and reconstruction with forehead flap as single modality treatment. Material and Methods. This is a retrospective review of 50 patients who underwent surgical excision of BCC involving the facial region followed by primary reconstruction using forehead flaps at a single institution. There were 20 males and 30 females, mean age of 59 years. Results. No recurrence at primary site was observed during the follow-up of 1–4 yrs. There was no ectropion or exposure sequela. However, epiphora was evident. Size of lesions ranged from 2 to 6 cm. Keloid formation was seen in 2 (4%) patients. Functional and cosmetic outcomes were satisfactory. Conclusion. For the face, the best reconstructive effort eventually fails in the face of tumor recurrence. The forehead flap represents one of the best methods for repair of extensive facial defects. Complete tumor extirpation, the primary event, is the key.